2017
DOI: 10.1590/1414-431x20165892
|View full text |Cite
|
Sign up to set email alerts
|

Influence of schooling and age on cognitive performance in healthy older adults

Abstract: Few studies have examined the influence of a low level of schooling on age-related cognitive decline in countries with wide social and economic inequalities by using the Cambridge Automated Neuropsychological Test Battery (CANTAB). The aim of the present study was to assess the influence of schooling on age-related cognitive decline using unbiased cognitive tests. CANTAB allows cognitive assessment across cultures and education levels with reduced interference of the examiner during data acquisition. Using two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 31 publications
(40 reference statements)
7
32
2
4
Order By: Relevance
“…The influence of lower levels of schooling in older adults is a theme found in current research 27,28 . This is relevant, especially in developing countries where a significant number of older adults have limited education 23,29 .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The influence of lower levels of schooling in older adults is a theme found in current research 27,28 . This is relevant, especially in developing countries where a significant number of older adults have limited education 23,29 .…”
Section: Discussionmentioning
confidence: 80%
“…A study carried out in Brazil with 167 elderly individuals reported that participants with lower education levels showed worse results for visual attention, reaction time, and learning skills. Moreover, it suggested that lower levels of educational achievement during the early stages of life is a greater risk factor than aging for cognitive decay 27 . Another study, using clinical data from three longitudinal studies in England, Wales and Finland, found that individuals with higher formal education during the early part of their life showed a reduction in the risk of clinical dementia 31 .…”
Section: Discussionmentioning
confidence: 99%
“…2017) and that low level of education may accentuate cognitive decline (Bento‐Torres et al . 2017); measures that enable the full inclusion of children with DS in school represent an important strategy to increase the quality of life of these individuals (Santos et al . 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between PAL performance and age is supported by existing literature showing an age-dependent decline in episodic memory and by studies using CANTAB PAL both within, and independently of, the TwinsUK cohort [61][62][63] . Increased education also showed significant effects on cognition but despite recent studies, it remains unclear whether this is due to cognitive reserve or a confounding effect of higher cognitive abilities increasing the likelihood of further education [64][65][66][67] .…”
Section: Discussionmentioning
confidence: 98%